Tecnologias digitais e emergência de zonas de desenvolvimento proximal na sala de aula - Arruda, Juliana Silva (2016)
Brazil is experiencing a period of technological immersion in all areas of society and every day, technologies are created that power the various human activities. The school should monitor the resulting changes of technological resources and be open to new educational possibilities to develop contemporary practices, from the inclusion of computers in school activities. Computers are features that enable interaction in group activities, the exchange of ideas and opinions; or the research of other realities. Thus, this study aims to analyze how the computer through digital resources used in activities collaboratively, can emerge Proximal Development Zone (ZDP). This research was developed in a municipal school in Aquiraz / CE, in groups of two or more learners. Qualitative methodology with interpretative character was used. The research technique involved participant observation, with micro genetic analysis and as tools for collecting videos and daily data field. Planned activities included the curriculum subjects, the use of computer and some Internet resources. The methodological procedures were considered from a micro genetic approach, and defined with the statement of contemporary researchers, as Meira and Lerman (2009) and Colaco et al. (2007) which expanded and interpreted new concepts of the ZDP Vygotsky (1994). The results were analyzed according to categories at the time of data analysis. In the first category, interaction among peers, was detailed as group activities, and peer contribution contributed to the development of the zone. In the second category, interaction with someone more experienced, involved contributions and assistance from someone more experienced, contributing to facilitating learning. The next third, technology support, has detailed the use of technology by students and contributions of this resource for teaching and learning processes. In the last category, student Protagonism discussed how students managed to overcome their level of development and can act as author of knowledge itself, and observed two characteristics: Activism and autonomy. The results highlighted times when resources combined with peer interaction promote and facilitate the emergence of ZPD, resulting in learning, promoting performances and authoring postures of these learners in the process.